The effect of using immediate and delayed feedback on learning the skills of passing and shooting in football (Journal of Hama University, 2022)
The problem of the research was determined by choosing the educational method, which must be compatible with the given mathematical skill on the one hand, and suit the age and ability of the learners on the other hand. From previous experience, if any, The research aims to identify the effect of immediate feedback in teaching the skills of passing and shooting in football, and to identify the effect of delayed feedback in teaching the skills of passing and shooting in football. The researcher also imposed that there is a positive effect of immediate feedback in teaching the skills of passing and shooting in football. There is also a positive effect of delayed feedback in teaching the skills of passing and shooting in football. The researcher used the experimental method by designing (the two equal groups with a pre and posttest).This is due to its relevance to the nature of the problem and the achievement of the research objectives. As for the research sample, it included the first year students of the Faculty of Physical Education, Hama University, who numbered (30) students. The most important conclusions were that the immediate and delayed feedback works on learning and developing the basic skills (passing - shooting) in football. Immediate and delayed feedback also has a positive effect on learning motor skills. The researcher recommended emphasizing the importance of immediate and delayed feedback in learning basic football skills. Emphasis on the importance of providing instructions to learners during practical lessons.